ANALYSIS OF FIGHTING FACTORS AS A PREVENTIVE EFFORT BY OFFICERS AT CLASS IIA NARCOTICS PENITENTIARY YOGYAKARTA - Ahmad, Naufal; Kurniawan, Andi (Universitas Nusa Cendana, 2025)
This study aims to identify the factors that influence fights among inmates and the preventive measures taken by officers to prevent such incidents. The research uses a qualitative approach, with data collected through interviews, observations, and document analysis. The findings show that fights are often triggered by factors such as revenge, economic problems, and conflicts of interest. Additionally, the preventive measures carried out by officers include increased supervision, mediation, and rehabilitation activities aimed at creating a safe and conducive environment. This research is expected to contribute to the development of strategies for preventing fights in correctional institutions and to enhance the effectiveness of officers in maintaining security and order. Keywords: Fights; Inmates; Preventive Measures; Narcotics Prison; Security